Empagliflozin Decreases Lactate Generation in an NHE-1 Dependent Fashion and Increases α-Ketoglutarate Synthesis From Palmitate in Type II Diabetic Mouse Hearts - Zhang, Hong; Uthman, Laween; Bakker, Diane; Sari, Sahinda; Chen, Sha; Hollmann, Markus W.; Coronel, Ruben; Weber, Nina C.; Houten, Sander M.; van Weeghel, Michel; Zuurbier, Coert J. (Frontiers in Cardiovascular Medicine, 2020)
Aims/hypothesis: Changes in cardiac metabolism and ion homeostasis precede and drive cardiac remodeling and heart failure development. We previously demonstrated that sodium/glucose cotransporter 2 inhibitors (SGLT2i’s) have direct cardiac effects on ion homeostasis, possibly through inhibition of the cardiac sodium/hydrogen exchanger (NHE-1). Here, we hypothesize that Empagliflozin (EMPA) also possesses direct and acute cardiac effects on glucose and fatty acid metabolism of isolated type II diabetes mellitus (db/db) mouse hearts. In addition, we explore whether direct effects on glucose metabolism are nullified in the presence of a NHE-1 inhibitor. Methods: Langendorff-perfused type II diabetic db/db mouse hearts were examined in three different series: 1: 13C glucose perfusions (n=32 ); 2: 13C palmitate perfusions (n=13); and 3: 13C glucose + 10 M Cariporide (specific NHE-1 inhibitor) perfusions (n=17). Within each series, EMPA treated hearts (1 M EMPA) were compared with vehicle-perfused hearts (0.02% DMSO). Afterwards, hearts were snap frozen and lysed for stable isotope analysis and metabolomics using LC-MS techniques. Hearts from series 1 were also analyzed for phosphorylation status of AKT, STAT3, AMPK, ERK, and eNOS (n=8 per group). Results: Cardiac mechanical performance, oxygen consumption and protein phosphorylation were not altered by 35 min EMPA treatment. EMPA was without an overall acute and direct effect on glucose or fatty acid metabolism. However, EMPA did specifically decrease cardiac lactate labeling in the 13C glucose perfusions (13C labeling of lactate: 58 ± 2% vs 50 ± 3%, for vehicle and EMPA, respectively; P=0.02), without changes in other glucose metabolic pathways. In contrast, EMPA increased cardiac labeling in α-ketoglutarate derived from 13C palmitate perfusions (13C labeling of α-KG: 79 ± 1% vs 86 ± 1% for vehicle and EMPA, respectively; P=0.01). Inhibition of the NHE by Cariporide abolished EMPA effects on lactate labeling from 13C glucose. Conclusions: The present study shows for the first time that the SGLT2 inhibitor Empagliflozin has acute specific metabolic effects in isolated diabetic hearts, i.e. decreased lactate generation from labeled glucose and increased α-ketoglutarate synthesis from labeled palmitate. The decreased lactate generation by EMPA seems to be mediated through NHE-1 inhibition.